Interpreting history through pictorial documents - Malan, Nancy; Malan, Nancy; Loy, John.; Duncan, Mike.; American Association for State and Local History; Scene Three/Nashville. ([S.l. s.n.)
A lecture on the variety of pictorial materials, their source, use, and presentation.
VHS
Keywords: Archival materials -- Exhibitions; Archives